Uji Kualitas Mikrobiologis Pada Makanan Jajanan di Kampus II Universitas Islam Negeri (UIN) Alauddin Makassar - Lasinrang Aditia; Cut Muthiadin (Department of Biology, Faculty of Sci and Tech, Universitas Islam Negeri Alauddin Makassar, 2015)
This study aimed to determine the microbiological quality of street food at campus II State Islamic University (UIN) Alauddin Makassar. This descriptive research describes contaminant Coliform bacteria and Escherichia coli in a sample street food in Campus II UIN Alauddin Makassar through Microbiological test. Counting the number of Coliform bacteria found in street food and Escherichia coli found in snack through methods Coliform MPN (Most Probable Number). The research was conducted at the Center for Health Laboratory Makassar (BBLK). These results obtained for Coliform MPN showed that levels of total Coliform bacteria were highest in Siomay code C = > 1,100 Coliform/g, this means that the sample does not qualify because it is not in accordance with the National Standards Board and ISO-7388-2009 the maximum limit value = 10 Coliform MPN/g. In Siomay code A = 240 Coliform/g, Batagor code B = 1.100 Coliform/g, and meatball code D = > 1,100 Coliform/g. Thus, it was concluded that this value is generally illustrates that coliform bacteria content in snack foods sold in the Campus II UIN Alauddin Makassar, low quality and already exceeds the threshold required quality standard that is healthy and nutritious food for our body. The MPN of Escherichia coli showed that the total levels of Escherichia coli are the highest in Siomay code C = > 1,100 E. coli/g, this means that the sample does not qualify because it is not according to the National Standardization Agency and SNI 7388-2009 which limits Escherichia coli MPN maximum value = < 3 E. coli/g. In Siomay code A = 240 E.coli/g, Batagor code B = 3,6 E. coli/g, and meatball code D => 120 E. coli/g. Thus, it was concluded that this value is generally illustrates that the content of Escherichia coli in street food sold in the Campus II UIN Alauddin Makassar, low quality and already exceeds the threshold.Keywords: Coliform, Escherichia coli, microbiological quality, Most Probable Number (MPN)